ADAPTASI TEKNIK LINEAR DRUM CHOPS DALAM LAGU YOU ARE GOOD DI SAJIAN LITURGI GBI KELUARGA ALLAH SURAKARTA - Christ Haryanta Person; Bondan Aji Manggala (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2022)
The research entitled "Adaptation of the Drum Chops Technique in the Song You Are Good in the Liturgical Serving of GBI Keluarga Allah Surakarta" was proposed by raising the assumption that this phenomenon occurs consciously and is related to many things in religious and cultural life in GBI Keluarga Allah Surakarta. There are two problem formulations, namely; 1) Why was gospel music adapted with drum chops technique in liturgical music at GBI Keluarga Allah Surakarta? 2) How was gospel music adapted and drum chops technique adapted to liturgical music at GBI Keluarga Allah Surakarta? and 3) How is the position of gospel music with drum chops technique in worship at GBI Keluarga Allah? The theory of cross-cultural adaptation is used as the basis for the analysis of this research by applying qualitative methods of field research techniques. The results of this study indicate that the GBI Keluarga Allah consciously accepts the gospel flow and uses Contemporary Christian Music (CCM) as the dominant music style because the concept of using liturgical music in GBI Keluarga Allah is a reference to the popular gospel music genre. The adaptation process that occurs in applying the linear drum chops technique is at least three things, namely simplification, mixing, and complicating the game references that are absorbed by the drummer through social media. The adjustment of the drum chops game is considered sufficient to affect the achievement of the desired atmosphere as in the part of the worship service.